PENGARUH PELATIHAN TERHADAP KOMPETENSI KARYAWAN PT. LEN INDUSTRI (PERSERO) BANDUNG - Wisastra, Putu Ifo Yuda; Sagala, Ella Jauvani (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2016)
This study aimed to analyze the influence of training on employee’s competency. This study was conducted at PT. Len Industri (Persero) Bandung. The sampling was using Slovin’s techniques with error rate 5%.The data analysis was using Path Analysis for this research and processed by using SPSS software ver.20 for windows. Data obtained by questionnaires to 192 employee respondents of PT. Len Industri (Persero) Bandung. The result showed that training variables had a significant influence on employee’s competency with simultaneously. But in partially, there’s didn’t have a significant influence on the employee’s competency. The variables that didn’t have a significant influence were training materials and trainees.
Keywords: human resources, training, competency